MAG2 and MAL Regulate Vesicle Trafficking and Auxin Homeostasis With Functional Redundancy - Ma, Xiaohui; Zhao, Xiaonan; Zhang, Hailong; Zhang, Yiming; Sun, Shanwen; Li, Ying; Long, Zhengbiao; Liu, Yuqi; Zhang, Xiaomeng; Li, Rongxia; Tan, Li; Jiang, Lixi; et al. (Frontiers in Plant Science, 2022)
Auxin is a central phytohormone and controls almost all aspects of plant development and stress response. Auxin homeostasis is coordinately regulated by biosynthesis, catabolism, transport, conjugation and deposition. ER-localized MAG2 complex mediates tethering of arriving vesicles to the ER membrane, and is crucial for ER export trafficking. Despite MAG2 important regulatory roles on vesicle trafficking, the mag2 mutants had mild developmental abnormalities. MAG2 has one homologue protein, MAL, and the mal-1 mutant also had slight developmental phenotypes. In order to investigate MAG2 and MAL regulatory function on plant development, we generated mag2-1 mal-1 double mutant. As expected, the double mutant exhibited serious developmental defects and more alteration on stress response compared with single mutants and wild type. Proteomic analysis revealed that signaling, metabolism and stress response in mag2-1 mal-1 were affected, especially membrane trafficking and auxin biosynthesis, signalling and transport. Biochemical and cell biological analysis indicated that mag2-1 mal-1 double mutant had more serious defects on vesicle transport than mag2-1 and mal-1 single mutants. And the auxin distribution and abundance of auxin transporters were altered significantly in mag2-1 and mal-1 single mutants and mag2-1 mal-1 double mutant. Our findings suggest that MAG2 and MAL regulate plant development and auxin homeostasis via controlling membrane trafficking, with functional redundancy.